The influence of Experiential Marketing and Brand Trust on Customer Satisfaction and Customer Loyalty Hotel Aryaduta Pekanbaru - Deny Danar Rahayu (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
This study aims to analyze the influence of Experiential Marketing and Brand Trustvariables on Customer Satisfaction and Customer Loyalty. This research wasconducted on the customers of Hotel Aryaduta Pekanbaru. Where these customershave to more than 1 times stay at Hotel Aryaduta Pekanbaru. In this study consistsof four variables, namely one dependent variable, one intervening variable and twoindependent variables. The variables are Customer Loyalty (Y2), CustomerSatisfaction (Y1), Brand Trust (X2), and Experiential Marketing (X1). This studywas conducted using a sample of 100 people. This research uses simple randomsampling technique that is taking the sample member from the population is donerandomly without considering the strata in the population. This is done whenmembers of the population are considered homogeneous. While in terms of dataanalysis, this study uses Path Analysis method with the help of SPSS (StatisticalPackage of Social Science) version 20. Based on Hypothesis test conducted, Theresults showed that Experiential Marketing and Brand Trust have positive andsignificant impact on Customer Satisfaction and Customer Loyalty .Keywords: Experiential Marketing, Brand Trust, Customer Satisfaction, Customer Loyalty.